Intravenous albumin infusion is an effective therapy for hyponatraemia in cirrhotic patients with ascites. Issue 2 (February 1990) - McCormick, P A; Mistry, P; Kaye, G; Burroughs, A K; McIntyre, N
Abstract : The treatment of moderate to severe hyponatraemia in patients with decompensated liver disease is unsatisfactory. We report our preliminary experience using intravenous infusion of albumin to treat this condition. Three patients with cirrhosis, ascites, and hyponatraemia responded satisfactorily to treatment; one patient with fulminant hepatitis B did not respond. Intravenous albumin infusion is a safe and effective therapy for patients with cirrhosis complicated by hyponatraemia. Its main role may be in preparing patients for surgery, particularly liver transplantation.